A Multimodal Approach to Álvaro Cunqueiro’s Journalistic Literature : Faro de Vigo (1961-1981) - Domínguez Romero, Elena (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
An analysis of the Spanish Press during the fifties and sixties allows us to approach the Spanish society of the time, which inevitably reflects the social, political and ideological situation of the Spanish state after the Civil war. In the following pages, we will basically decipher the role of images and captions in the literary column ‘El Envés’ [The Other side (of news)], published by Álvaro Cunqueiro over twenty years in the Faro de Vigo, as well as the importance of these images in the regeneration of Galician culture during Francoism. In order to do so, we will analyse the role of these images in the whole communicative process in the journal under a very specific perspective: the multimodal approach.